A grid-based facilities allocation approach with safety and optimal heat exchanger networks synthesis. (2nd September 2015) - Vázquez-Román, Richart; Inchaurregui-Méndez, José A.; Mannan, M. Sam
Highlights: A combined model for HEN synthesis and facility layouts is developed in this work. Process safety is incorporated to provide safety in HEN and facility layouts with toxic releases. A grid-based siting allocation is used and a new approach is developed to reduce numerical problems. The three dimensions for geographical allocation of each generated stream are included in the model. Abstract: A new approach is presented to determine optimal layout of facilities where toxic releases may occur in an existing or new facility. The land area is divided in equally sized rectangular grids, where each grid contains up to one facility surrounded by streets. Some facilities may produce hot and/or cold streams and the associated heat exchangers network (HEN) is simultaneously optimized with the layout problem. The three dimensions of geographical allocation points for each generated stream are included in the model. No additional cost for geographical allocation of heating and cooling services is considered since every facility is expected to contain these services regardless of their use in the HEN. The toxic effect is estimated via probit functions and its associated risk reduction results in providing safety to the combined HEN-facility layout problem. The grid-based allocation eliminates numerical difficulties appearing with conventional non-overlapping and Euclidian distance equations.